Learn more about

Refine search

Results (displaying matches 1-50 of 276) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
6081.b.164187.1 6081.b \(y^2 + (x^3 + x^2 + 1)y = -2x^4 - 5x^3 + 5x + 2\) $\mathrm{USp}(4)$ 2
6400.f.64000.1 6400.f \(y^2 + x^3y = -2x^4 - 3x^3 + x^2 + 6x + 4\) $E_4$ 2
12588.a.151056.1 12588.a \(y^2 + y = x^6 - 2x^4 + 2x^2 - x\) $\mathrm{USp}(4)$ 2
12996.a.467856.1 12996.a \(y^2 + y = x^6 + 2x^4 - x^2\) $G_{3,3}$ 2
13580.b.950600.1 13580.b \(y^2 + (x^3 + x + 1)y = 3x^5 + 3x^4 - x^2 - x\) $\mathrm{USp}(4)$ 2
22020.b.660600.1 22020.b \(y^2 + (x^3 + x + 1)y = 2x^5 - 5x^3 + x\) $\mathrm{USp}(4)$ 2
26756.a.428096.1 26756.a \(y^2 + (x^3 + x^2 + x)y = x^4 - 3x^2 - x + 1\) $\mathrm{USp}(4)$ 2
38052.a.684936.1 38052.a \(y^2 + (x^3 + x + 1)y = 8x^3 + 16x^2 + 10x + 2\) $\mathrm{USp}(4)$ 2
39017.a.39017.1 39017.a \(y^2 + (x^3 + x + 1)y = -x^5 + x\) $\mathrm{USp}(4)$ 3
44543.a.44543.1 44543.a \(y^2 + (x^3 + x + 1)y = x^4 - x^2\) $\mathrm{USp}(4)$ 3
53623.a.53623.1 53623.a \(y^2 + (x^2 + x + 1)y = x^6 - 2x^4 + x^3 - 2x\) $\mathrm{USp}(4)$ 3
56473.a.56473.1 56473.a \(y^2 + (x^3 + x^2 + x)y = -2x^4 + x^3 - 2x + 1\) $\mathrm{USp}(4)$ 3
56629.a.56629.1 56629.a \(y^2 + (x^2 + x + 1)y = x^6 - x^2\) $\mathrm{USp}(4)$ 3
59411.a.59411.1 59411.a \(y^2 + y = x^6 - x^5 - x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 3
61099.a.61099.1 61099.a \(y^2 + (x^3 + 1)y = -3x^4 + 3x^3 + 2x^2 - 2x\) $\mathrm{USp}(4)$ 3
64829.a.64829.1 64829.a \(y^2 + (x^3 + x + 1)y = x^4 + x^3 + x^2 + x\) $\mathrm{USp}(4)$ 3
65167.b.65167.1 65167.b \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 5x^3 - 2x^2 + x\) $\mathrm{USp}(4)$ 3
66601.a.66601.1 66601.a \(y^2 + (x^3 + 1)y = -x^4 + 5x^3 + 16x^2 + 11x + 2\) $\mathrm{USp}(4)$ 3
71957.a.71957.1 71957.a \(y^2 + (x^3 + x + 1)y = 3x^3 + 5x^2 + 2x\) $\mathrm{USp}(4)$ 3
73753.a.73753.1 73753.a \(y^2 + (x^3 + 1)y = -x^4 - 2x\) $\mathrm{USp}(4)$ 3
76414.a.152828.1 76414.a \(y^2 + (x^3 + x)y = x^5 - 4x^3 - 7x^2 + 4\) $\mathrm{USp}(4)$ 3
78193.b.78193.1 78193.b \(y^2 + y = x^6 - 5x^5 + 7x^4 - 5x^2 + 2x\) $\mathrm{USp}(4)$ 3
78947.b.78947.1 78947.b \(y^2 + (x^3 + x^2 + 1)y = 2x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 3
79337.a.79337.1 79337.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - x^2 - 3x + 2\) $\mathrm{USp}(4)$ 3
81443.a.81443.1 81443.a \(y^2 + y = x^6 - x^5 - 2x^4 + x^2 + x\) $\mathrm{USp}(4)$ 3
87379.a.87379.1 87379.a \(y^2 + (x^3 + 1)y = -2x^4 + 2x^3 - x^2 + x\) $\mathrm{USp}(4)$ 3
87767.a.87767.1 87767.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 - 3x^2 + x\) $\mathrm{USp}(4)$ 3
88015.a.440075.1 88015.a \(y^2 + (x^2 + x + 1)y = x^6 + 2x^5 + 2x^4 - x\) $\mathrm{USp}(4)$ 3
88034.a.176068.1 88034.a \(y^2 + (x^3 + 1)y = 2x^5 - 10x^4 + 11x^3 - 2x^2 - x\) $\mathrm{USp}(4)$ 3
88149.a.264447.1 88149.a \(y^2 + y = x^6 - x^5 + 3x^4 - 3x^3 + 3x^2 - x\) $\mathrm{USp}(4)$ 3
88377.a.265131.1 88377.a \(y^2 + (x^3 + x^2 + 1)y = -2x^3 - 5x^2 + x + 6\) $\mathrm{USp}(4)$ 3
88405.a.88405.1 88405.a \(y^2 + y = x^6 - x^5 - 2x^4 + x^3 + 2x^2 - x\) $\mathrm{USp}(4)$ 3
89339.a.89339.1 89339.a \(y^2 + (x^3 + 1)y = 2x^5 + 4x^4 + x^3 - x^2 - x\) $\mathrm{USp}(4)$ 3
91427.a.91427.1 91427.a \(y^2 + (x^3 + x^2 + 1)y = 2x^4 + 3x^3 - x\) $\mathrm{USp}(4)$ 3
91457.a.91457.1 91457.a \(y^2 + (x^3 + x + 1)y = x^3 - 3x^2\) $\mathrm{USp}(4)$ 3
92482.a.184964.1 92482.a \(y^2 + (x^3 + x^2 + x)y = x^4 + x^3 + x + 1\) $\mathrm{USp}(4)$ 3
93154.a.186308.1 93154.a \(y^2 + (x^3 + x^2 + x)y = 2x^2 + x + 1\) $\mathrm{USp}(4)$ 3
93253.a.93253.1 93253.a \(y^2 + (x^3 + x + 1)y = -3x^2 - x + 2\) $\mathrm{USp}(4)$ 3
93953.a.93953.1 93953.a \(y^2 + (x^3 + x + 1)y = 4x^3 + 5x^2 + x\) $\mathrm{USp}(4)$ 3
97693.b.97693.1 97693.b \(y^2 + x^3y = 6x^3 + 13x^2 + 9x + 2\) $\mathrm{USp}(4)$ 3
98837.a.98837.1 98837.a \(y^2 + x^3y = 2x^2 - 3x + 1\) $\mathrm{USp}(4)$ 3
99361.a.99361.1 99361.a \(y^2 + (x^2 + x + 1)y = x^6 - x^4 + x^3 - x\) $\mathrm{USp}(4)$ 3
101254.a.202508.1 101254.a \(y^2 + xy = x^6 - x^5 - x^4 + 2x^3 - x^2 - x + 1\) $\mathrm{USp}(4)$ 3
101291.a.101291.1 101291.a \(y^2 + (x^3 + x^2 + x + 1)y = 4x^3 + 5x^2 - 3x\) $\mathrm{USp}(4)$ 3
101833.a.101833.1 101833.a \(y^2 + (x^3 + 1)y = -x^4 + x^3 - 6x + 6\) $\mathrm{USp}(4)$ 3
102347.a.716429.1 102347.a \(y^2 + x^3y = -x^4 - x^3 + 6x^2 - 5x + 1\) $\mathrm{USp}(4)$ 3
102553.a.102553.1 102553.a \(y^2 + (x^3 + x + 1)y = 2x^4 + 3x^3 + x^2\) $\mathrm{USp}(4)$ 3
102775.a.513875.1 102775.a \(y^2 + y = x^6 - 5x^5 + 6x^4 + x^3 - x\) $\mathrm{USp}(4)$ 3
104948.a.209896.1 104948.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^4 + x^2 - 2x\) $\mathrm{USp}(4)$ 3
106823.a.106823.1 106823.a \(y^2 + x^3y = -x^4 - 2x^3 + x^2 + 3x + 1\) $\mathrm{USp}(4)$ 3
Next

Download all search results for